International Handbook of School Effectiveness and Improvement - Townsend, Tony.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This handbook provides the most comprehensive international review of the school effectiveness and school improvement research in the twenty five years since the disciplines became prominent. The handbook contains chapters, not only from most of the key contributors to this research from the USA, the UK, Hong Kong and Europe, but also contains a number of chapters that document the progress of the field in regions of the world that are less known, including the Asian-Pacific region, Latin America, Africa and the Middle East. It contains the thoughts of not only the proponents of school effectiveness research, but those that have been critical of it. It documents the progress of the field over the past quarter century and clearly identifies the improvements in research techniques and the ability to consider context as a major feature. It provides both theoretical constructs and practical applications and case studies that are transnational and those that are local. Finally, it provides some possibilities for future research, policy and practice to guide the discipline into the next decade of change. The handbook provides a state of the art analysis of the complex issues facing schools, school systems, societies and nations that will support researchers, policy makers and practitioners in their search for ways to provide a high quality education to all students.
A Review of the Progress -- 20 Years of ICSEI: The Impact of School Effectiveness and School Improvement on School Reform -- Four Decades of Body-Surfing the Breakers of School Reform: Just Waving, Not Drowning -- Generic and Differentiated Models of Educational Effectiveness: Implications for the Improvement of Educational Practice -- Improving School Effectiveness: Retrospective and Prospective -- School Effectiveness Research in Latin America -- "Effective for What; Effective for Whom?" Two Questions SESI Should Not Ignore -- Pursuing the Contextualisation Agenda: Recent Progress and Future Prospects -- A World Showcase: School Effectiveness and Improvement from all Corners -- A History of School Effectiveness and Improvement Research in the USA Focusing on the Past Quarter Century -- History of the School Effectiveness and Improvement Movement in Canada over the Past 25 Years -- School Improvement in Latin America: Innovations over 25 Years (1980-2006) -- Growing Together: School Effectiveness and School Improvement in the UK -- Educational Effectiveness and Improvement: The Development of the Field in Mainland Europe -- School Effectiveness and Improvement in Asia: Three Waves, Nine Trends and Challenges -- School Effectiveness and Improvement in Taiwan -- School Effectiveness and Improvement in Mainland China -- The Maturing of a Movement: Tracking Research, Policy and Practice in Australia -- Schooling Reform: Reflections on the New Zealand Experience -- History of the School Effectiveness and Improvement Movement in Africa -- School Autonomy for School Effectiveness and Improvement: The Case of Israel -- Recent Initiatives in School Effectiveness and Improvement: The Case of Turkey -- Recent Initiatives in School Effectiveness and Improvement: The Case of the Islamic Republic of Iran -- Resources, School Effectiveness and Improvement -- The Relationship Between Student Attainment and School Resources -- Accountability, Funding and School Improvement in Canada -- Cost and Financing of Education and Its Impact on Coverage and Quality of Services and Efficiency and Equity in Sub-Saharan African Countries -- Resources and School Effectiveness and Improvement -- Accountability and Diversity, School Effectiveness and Improvement -- School Effectiveness and School Improvement (SESI): Links with the International Standards/Accountability Agenda -- Evolution of School Performance Research in the USA: From School Effectiveness to School Accountability and Back -- Education Decentralisation and Accountability Relationships in Latin American and the Caribbean Region -- Equity, Efficiency and the Development of South African Schools -- Policy Perspective on School Effectiveness and Improvement at the State Level: The Case of South Australia -- Diverse Populations and School Effectiveness and Improvement in the USA -- Changing Schools Through Strategic Leadership -- School Leadership, School Effectiveness and School Improvement: Democratic and Integrative Leadership -- Leadership and School Reform Factors -- The Emotional Side of School Improvement: A Leadership Perspective -- Leadership and School Effectiveness and Improvement -- Leadership Development for School Effectiveness and Improvement in East Asia -- Changing Teachers and Classrooms for School Improvement -- Teacher Leadership: Barriers and Supports -- The Continuing Professional Development of Teachers: Issues of Coherence, Cohesion and Effectiveness -- The Evolving Role of Teachers in Effective Schools -- Teacher Education and Professional Development for Sustainable School Effectiveness -- School and Teacher Effectiveness: Implications of Findings from Evidence-Based Research on Teaching and Teacher Quality -- System Supports for Teacher Learning and School Improvement -- Curriculum Reforms and Instructional Improvement in Asia -- Models of School Improvement -- Effective School Improvement - Ingredients for Success: The Results of an International Comparative Study of Best Practice Case Studies -- Self-Directed Learning as a Key Approach to Effectiveness of Education: A Comparison among Mainland China, Hong Kong, Macau, and Taiwan -- Coming and Going: Educational Policy and Secondary School Strategy in the Context of Poverty - Latin American Case Studies -- The School Review Process: The Case of the British Schools in Latin America -- Inquiry-Based Science Education and Its Impact on School Improvement: The ECBI Program in Chile -- Creating New Schools Using Evidence Based Solutions - A Case Study -- Best Practice in Secondary School Improvement: The Case of Salisbury High School -- Learning from the Past to Reframe the Future -- School Effectiveness and Improvement in the Twenty-First Century: Reframing for the Future.
Keywords: EDUCATION; COMPARATIVE EDUCATION; EDUCATION AND STATE; EDUCATION; COMPARATIVE EDUCATION; LEADERSHIP & ADMINISTRATION; EDUCATIONAL POLICY